Features of the implementation of the all-union physical culture and sports complex GTO at the regional level - Bobkova E.N.; Zyurin E.A.; Kireeva A.V.; Vrublevskiy E.P. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to based on statistical reporting, is to analyze the organizational and managerial conditions for the implementation of the VFSK GTO in the constituent entities of the Russian Federation for 2022 and to identify the level of physical fitness of the countrys population. Methods and structure of the study. The following methods were used: sociological (questioning, content analysis), study and analysis of federal statistical reporting of 85 regions of the Russian Federation, observation, comparison, mathematical and statistical processing of the results obtained. The research was carried out on the basis of the Federal State Budgetary Institution «Federal Scientific Center for Physical Culture and Sports» and the scientific and methodological center for the implementation of the VFSK «Ready for Labor and Defense» of the Federal State Budgetary Educational Institution of Higher Education «Smolensk State University of Sports», which, as part of the scientific and methodological support of the industry, have been established since 2017. annually monitor the implementation of the WFSK GTO in the Russian Federation. Results and conclusions. Multi-level monitoring made it possible to systematically and objectively evaluate management decisions within the framework of the implementation of this complex in the country, and annual statistical information to monitor the target indicators of the Strategy for the Development of Physical Culture and Sports in the Russian Federation, to identify problematic areas and development prospects, to assess the results of physical culture, sports and recreational activities, training and work of personnel, as well as determine indicators of physical fitness of various population groups.